Reimagining Rural Literacy Spaces: Lessons from a Community-Based Reading Corner in a Serang Regency Village - Lilis Hoeriyah (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: Indonesia's literacy culture remains at a concerning level, with the PISA survey placing the country 62nd out of 70 nations. Sukajaya Village reflects this challenge, characterized by limited access to high-quality reading materials and high levels of gadget dependency among children. Purpose of the Study: This study aims to analyze the strategies employed by the local community to optimize the Reading Corner as a sustainable and self-reliant center for non-formal education. Methods: The initiative utilized a descriptive qualitative approach, applying Participatory Action Research (PAR) and Asset-Based Community Development (ABCD) through a 5D cycle: Define, Discovery, Dream, Design, and Deliver. Results: The program successfully strengthened literacy governance by mobilizing local assets and relocating the facility to a strategic, weather-protected residence of a local educator. Quantitatively, this intervention resulted in a significant increase in accessibility, with the number of weekly visitors rising from zero to an average of 20 children per week. Success was driven by participatory management, including the establishment of a Village Literacy Committee involving Karang Taruna youth and women activists. The emergence of local champions and increased parental support have ensured the program's sustainability. The study concludes that mobilizing social capital and internal village assets is more effective for rural literacy development than relying solely on external assistance.